Unlocking seismic slope stability for risk assessment - Yiheng, Wang; Mohamed Nazri, Fadzli; El-Maissi, Ahmad Mohamad; Rahmat, Siti Rahyla; Mohd Kassim, Azleena; Karuppayah, Shankar (MethodsX, 2025)
Slope instability represents a substantial secondary hazard post-earthquake, leading to considerable socio-economic losses from the destruction of structures, infrastructure, and human lives. This study addresses the urgent need for precise evaluation of seismic slope stability, a subject that has gained significant attention in earthquake engineering over the past decade. A theoretical framework is proposed that utilizes an improved Sarma method, estimating seismic forces and safety factors based on limit equilibrium theory. A Python-based implementation enhances both computational efficiency and reliability. The enhanced method is validated against the pseudo-static approach, exhibiting strong performance. Moreover, critical elements affecting slope stability, such as slope characteristics and seismic motion parameters, are examined. Although the findings predominantly concentrate on rocky slopes, next research intends to broaden the method's application to multiple slope types, hence facilitating more thorough and effective stability evaluations across different geological contexts.•Deriving seismic slope safety factors based on improved Sarma and Pseudo static methods.•Developing Python programs based on the improved Sarma safety factor method.•Assessing seismic rock slope stability based on calculated Safety Factors. [Display omitted]